Model Pembelajaran Kewirausahaan dalam Upaya Penyiapan Kerja pada Program Kesetaraan Kejar Paket C Di PKBM Bima Sakti Kabupaten Banyuwangi - Mubarok, Meidian Fauzi; Sutarto, Joko (Universitas Syiah Kuala, 2025)
This study aims to develop and test an integrated entrepreneurship learning model in the Equalization Program Package C at the Bima Sakti Kedayunan Community Learning Center (PKBM), Banyuwangi. This learning model aims to enhance the entrepreneurial skills of learners, most of whom are already working or have family responsibilities, so they are prepared to face the challenges of the job market or start their own business. This research uses a qualitative approach with a case study method, involving interviews, observations, and documentation. The results show that the factors supporting the implementation of the entrepreneurship learning model include partnerships with SMEs and the Business/Industrial World, adequate facilities and infrastructure, and relevant training. Meanwhile, the main challenges include issues with scheduling, the cost of practice materials, internet access, and limitations in the regulation of BOS fund usage. Based on these findings, the project-based learning model and partnerships with SMEs have a positive impact on learners' motivation and work readiness